Influence of Doping Zn on H2 Sensing Characteristics of Nickel Ferrite Nanoparticles - Nguyet, Dao Thi Thuy; Duong, Nguyen Phuc; Ngoc Anh, Luong (VNU Journal of Science: Mathematics - Physics; Vol 39 No 4DO - 10.25073/2588-1124/vnumap.4847, 2023)
In this work, H 2 gas sensors were prepared using nickel zinc ferrite NiFe 2 O 4 and Ni 0.5 Zn 0.5 Fe 2 O 4 nanoparticles, then the hydrogen gas sensing performance of the sensors was tested. The nickel zinc ferrite nanoparticles were synthesized by chemical co-precipitation combined with thermal annealing. Crystalline Structure and morphology characterization of synthesized powders was made by using X-ray diffraction (XRD) and Transmission electron microscopy  (TEM) analysis, respectively. Nano powder resulting from milling was used to prepare gas sensing elements in pellet form. The gas-sensing properties were studied in the presence of hydrogen as test gases. The gas response was found to be strongly influenced by the Zn substitution doping concentration in NiFe 2 O 4 . A significant high sensitivity of ~ 90% was found for the compound of Ni 0.5 Zn 0.5 Fe 2 O 4 . in the presence of 500 ppm H 2  at the operating temperature of 250 °C.